ANTIBACTERIAL AND DIASTASE ENZYME ACTIVITIES OF HONEY Apis mellifera FROM INDONESIA - Rara Annisaur Rosyidah; Akhmad Endang Zainal Hasan; Dimas Andrianto (BIOTROPIA, 2024)
The quality of monofloral honey from Apis mellifera as an antibacterial can be influenced by the activity of the diastase enzyme and the secondary metabolites from the nectar source. Therefore, this study aimed to compare the activity of the diastase enzyme and the effectiveness of monofloral honey derived from Apis mellifera bees as a natural antibacterial agent against Staphylococcus aureus and Escherichia coli. Sampling for monofloral honey was carried out from nine different nectar sources, namely Acacia carpa, Calliandra calothyrsus, Nephelium lappaceum, Melaleuca laucadendron, Ceiba pentandra, Mangifera indica, Coffea robusta 1, Coffea robusta 2, and Hevea brasiliensisensi. Furthermore, diastase content was determined using UV-Vis spectrophotometry and the bacterial inhibition zone using the disc diffusion method. The principal component analysis (PCA) was used to analyze the clustering of diastase enzyme and antibacterial activity. The results showed that the highest diastase activity in monofloral honey was Mangifera indica, Nephelium lappaceum, and Coffea robusta 2 at 20.00 DN. This was followed by Nephelium lappaceum, Ceiba pentandra, and Hevea brasiliensisensisensi at 10.00 DN, Acacia carpa at 6.67 DN, Coffea robusta 1 at 5.00 DN, and Calliandra calothyrsus 4.00 DN. The clear zones for Staphylococcus aureus on Coffea robusta 2, Acacia carpa, Nephelium lappaceum, Coffea robusta 1, Ceiba pentandra, Hevea brasiliensisensisensi, Nephelium lappaceum, Calliandra calothyrsus, and Mangifera indica were 19.47, 18.53, 17.73, 17.03, 16.12, 16.10, 16.03, 15.73, and 14.73 mm, respectively. Additionally, the clear zones for Escherichia coli on Ceiba pentandra, Coffea robusta 2, Acacia carpa, Coffea robusta 1, Melaleuca laucadendron, Mangifera indica, Hevea brasiliensisensisensi, Calliandra calothyrsus, and Nephelium lappaceum were 27.93, 26.13, 24.60, 24.53; 24.53, 24.07, 21.90, 21.60, and 21.53 mm, respectively. In conclusion, clustering analysis was conducted based on nectar sources to evaluate antibacterial and diastase activity. The clusters identified are cluster 1 consisting of Hevea brasiliensisensi, cluster 2 including Mangifera indica, and Nephelium lappaceum. Others are cluster 3 consisting of Acacia carpa and Calliandra calothyrsus, and clustergroup 4 including Nephelium lappaceum, Ceiba pentandra, Coffea robusta 1, and Coffea robusta 2. Therefore, it was necessary to carry out antibacterial testing of other bacteria, specifically Salmonella typhi, and determine the minimum inhibitory concentration (MIC) of honey with the best antibacterial activity in various concentration variations.